Factors that favor the adoption of soil conservation practices: evidence from Ecuadorian small farmers - Singaña, David (2021)
The modernization of agricultural practices with the purpose of increasing the productivity of a privileged group of crops has spread in South America since the 1970s. The main practices that were implemented included the use of fertilizers and phytosanitary control based on synthetic elements, and the agricultural mechanization for plowing. These activities directly affect the quality of soils, and make them more dependent on fertilizer imports throughout the continent. The intensification of agricultural activity also increased CO2 emissions in South America from less than 150 thousand gigagrams in 1977 to more than 280 thousand gigagrams in 2017, which translates into a greater burden of agriculture on the environment. Ecuador is one of the South American countries that has several common social, climatic and topographic characteristics in the region, therefore, it is interesting to study the factors that help to mitigate the processes of soil erosion resulting from agricultural activity. For this, this study performs the estimation of a Tobit model with the information of the agricultural production units with transitory crops present in the Survey of Surface and Continuous Agricultural Production of the year 2018.